Remoção de material obturador proporcionado por regimes de irrigação durante o retratamento endodôntico: análise por microtomografia - Oliveira, Eulália Mendes de (2023)
The present study evaluated the effect of irrigation and activation of irrigation solution as complementary methods to the removal of filling material during endodontic retreatment of mesial canals of lower molars (mesiobuccal and mesiolingual) with isthmuses. Thirty specimens were selected after initial analysis by computed microtomography and prepared following the same protocols for coronary access, cleaning, modeling and obturation. Once filled, the specimens were submitted to the removal of filling material. Removal of filling material was performed using Reciproc R25 and R40 instruments, in sequence, and associated with abundant irrigation with 2.5% sodium hypochlorite. Subsequently, the entire sample was subjected to a new scan in the microtomograph in order to quantify the remaining filling material. Once the remaining was quantified, the specimens were randomly divided into three groups depending on the final irrigation protocols: passive ultrasonic irrigation (PUI), continuous ultrasonic irrigation (CUI) and a control group that received only conventional irrigation (CON). Regardless of the group, 60 ml of irrigating solution were used for each root canal; this volume was divided into aliquots of 20 mL that were associated with activation cycles in the PUI/CUI groups. At the end of the complementation stage, the specimens were again submitted to microtomographic scanning, which allowed a new quantification of remaining material inside the root canals. The values found for the remaining obturators before and after the protocols employed were submitted to the normality test, which indicated a non- parametric nature. Then, the Wilcoxon test was applied, which indicated, in the three groups, a significant difference (P < 0.05). The percentage of reduction offered by the groups was also calculated, observing median values of 35.44% (CUI), 32.37% (PUI), and 26.03% (CON); the Kruskal-Wallis test did not observe significant differences between groups (P > 0.05). In view of the results presented, considering the conditions of the study, it can be concluded that carrying out an additional irrigation protocol, after clearing the canals, is fundamental for the additional removal of remaining filling material, however, the use of continuous ultrasonic agitation or passive, did not significantly influence this removal.